The Role Of Peer Volunteers In Building Learning MotivatThe Role Of Peer Volunteers In Building Learning Motivation Of Students With Disabilities At University of Bina Mandiri Gorontaloion Of Students With Disabilities At University of Bina Mandiri Gorontalo - Muhammad Marham Mubaraq Lumi Marham; Ali Alhasni Alhasni; Imam mashudi (Jurnal Ilmu Pendidikan dan Budaya, 2026)
Students with disabilities in higher education often encounter multifaceted challenges, including limited physical accessibility, persistent social stigma, and communication barriers, all of which significantly diminish their learning motivation. This qualitative study investigates the strategic role of Peer Volunteers in fostering academic motivation among students with disabilities at Universitas Bina Mandiri Gorontalo. Utilizing a case study design, data were gathered through in-depth interviews, field observations, and documentary analysis involving students with disabilities, volunteer coordinators, and the Head of the Disability Service Unit. The findings reveal that Peer Volunteers serve as a vital support system by providing academic assistance, emotional encouragement, and social bridging. This peer-to-peer intervention effectively reduces anxiety, enhances self-confidence, and promotes independence among students with disabilities. Furthermore, the study identifies that structured recruitment and specialized training for volunteers are essential for maintaining the quality of inclusive mentoring. The presence of Peer Volunteers not only overcomes technical learning obstacles but also cultivates a more inclusive campus culture. This research concludes that integrating peer mentoring programs into university policy is a fundamental strategy for promoting educational equality and ensuring the academic success of students with diverse needs.